Density of caalcareous macroalgae Halimeda sp. and Padina sp. around the water of Kodingareng Lompo Island, Spermonde Archipelago, Indonesia - Bakti, Nurqadri Syaia; Rukminasari, Nita; Yaqin, Khusnul; Nane, La; Yusuf, Muh Yusfi (Gorontalo State University, 2022)
Based on the results obtained from this study, it can be concluded that: (1). Halimeda sp density based on stations, there is a noticeable difference between station 1 and station 3, (2)Halimeda sp density based on the research time, namely there is a noticeable difference between the study time in July and October, (3) Padina sp density based on stations, there is a noticeable difference between station 1 and station 2, and (4). The density of Padina sp is based on the time of the study, that is, there is a noticeable difference between the time of the study in July and October.